(untitled) (Journal of NELTA, 2018)
Paragraph writing generally refers to developing a single idea on a given topic. I think teaching writing a paragraph is not a difficult task at basic and secondary levels (6-10 grades), as the students in Nepali context consider it as such. The skill used to write a paragraph could also be helpful even when one delivers speech on any of a number of topics. Writing a paragraph can be a joyful task if it follows a process-based model. This lesson focuses on teaching writing the paragraph while preparing teachers (pre-service) in post-secondary and bachelor’s level in the university to teach primarily at secondary level. Journal of NELTA , Vol. 22, No. 1-2, 2017 December, Page: 130-134